Turtles All the Way Down - Green, John, 1977- (New York, NY : Dutton Books, 2017)
"Sixteen-year-old Aza never intended to pursue the mystery of fugitive billionaire Russell Pickett, but there's a hundred-thousand-dollar reward at stake and her best and most fearless friend Daisy is eager to investigate. So together they navigate the short distance and broad divides that separate them from Russell Pickett's son Davis. Aza is trying. She is trying to be a good daughter, a good friend, a good student, and maybe even a good detective, while also living within the ever-tightening spiral of her own thoughts"--Dust jacket flap.
Includes bibliographical references.
Keywords: Teenage girls -- Juvenile fiction; Obsessive-compulsive disorder in adolescence -- Juvenile fiction; Anxiety disorders -- Juvenile fiction; Friendship in adolescence -- Juvenile fiction; Missing persons -- Juvenile fiction; Obsessive-compulsive disorder -- Fiction; Anxiety disorders -- Fiction; Friendship -- Fiction; Missing persons -- Fiction; YOUNG ADULT FICTION / Coming of Age; YOUNG ADULT FICTION / Social Themes / Friendship; YOUNG ADULT FICTION / Social Themes / Mental Illness; YA Fiction